The international regulation of herring, blue whiting and mackerel fishery - Krysov A. I.; Pronyuk A. A.; Rybakov M. O.; Kalashnikov Yu. N. (Vestnik MGTU, 2017)
The purpose of the fisheries management is to provide the conditions for long-term, high and sustainable fishing. Most of the fish stocks in the North-East Atlantic's are transboundary and straddling, and some international agreements in the field of regulation of their fishing are required for effective management. Achieving multilateral international agreements in the field of fisheries is very difficult and long-term process, because it affects the economic and political interests of the contracting parties. The paper considers results of the analysis of stock dynamics of the most important fishery resources in the North-East Atlantic – herring, blue whiting and mackerel – in different historical periods. As in the past few decades, we have seen periods of both managed and unmanaged fisheries and in relation to the value of stocks of pelagic fish there have been significant fluctuations, in this paper the authors have attempted to estimate the value of concerted international fisheries management to maintain a stable state of stocks of pelagic fish. Implementation of scientific recommendations agreed by the participating countries of ICES and the joint management of the herring stock management contribute to the preservation of stock stable and optimal levels of withdrawal of the object. The historical experience of the international fishing of blue whiting has shown that compliance by states involved in the fishery advice of ICES and its reserve management activities and promotes the good stock condition. To save the mackerel stock within safe biological boundaries it is necessary to achieve the agreed long-term plan for managing its fisheries between all participants in the fishery. In the long term for the conservation of stocks of herring, blue whiting and North East mackerel in the safe biological boundaries, the international regulation of their fisheries based on the scientific recommendations of ICES in the framework of NEAFC and the Consultations of Coastal States is necessary.